2021
DOI: 10.1007/s10586-021-03361-w
|View full text |Cite
|
Sign up to set email alerts
|

ProBlock: a novel approach for fake news detection

Abstract: The world is diving deeper into the digital age, and the sources of first information are moving towards social media and online news portals. The chances of being misinformed increase multifold as our reliance on sources of information are getting ambiguous. Traditional news sources followed strict codes of practice to verify stories, whereas today, users can upload news items on social media and unverified portals without proving their veracity. The absence of any determinants of such news articles’ truthful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Finally, we found that the presence of a call for action is associated with false rumors. Previous studies have also shown that calling for counteraction to create chaos could be the purpose of some rumors (83,84). Whether a rumor contains a call to retweet the information or a call to take counteraction against governmental prevention and curative policies may present an obstacle to implementing these policies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that the presence of a call for action is associated with false rumors. Previous studies have also shown that calling for counteraction to create chaos could be the purpose of some rumors (83,84). Whether a rumor contains a call to retweet the information or a call to take counteraction against governmental prevention and curative policies may present an obstacle to implementing these policies.…”
Section: Discussionmentioning
confidence: 99%
“…Their experiments mainly focus on the feasibility of the average response times of the system rather than how and how well the system identifies fake news. In [50], Sengupta et al propose ProBlock, which is a secure voting system with an emphasis on reviewer privacy.…”
Section: Related Workmentioning
confidence: 99%
“…The centralized social networks have problems such as data privacy leakage and unrestricted spreading of fake news, which greatly violate user privacy security and affect their ability to discern information ( Cadwalladr & Graham-Harrison, 2018 ). The unique decentralization, consensus mechanism, traceability and other features of blockchain can achieve a trustless and self-managed data interaction environment, which breaks through the technical bottleneck of existing social network management ( Hisseine, Chen & Yang , 2022 ; Sengupta et al , 2021 ). With the combination of blockchain technology and social networks, several social media platforms have emerged, such as Steemit , Lit , HyperSpace , Sapien , SocialX , FORESTING and Minds ( Guidi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%